Near-field characterization of micro/nano-scaled fluid flows - Kihm, Kenneth D. (Experimental Fluid Mechanics, 2011)
The near-field the region within 100 nm from a solid interface - is an exciting arena in which several important multi-scale transport phenomena are physically characterized, such as flow mixing and drag, heat and mass transfer, near-wall behavior of nanoparticles, the binding of bio-molecules, crystallization, and surface deposition processes, just to name a few. This book presents a number of microscopicimaging techniques that were implemented and tested for near-field fluidic characterizations. These methods include Total Internal Reflection Microscopy (TIRM), Optical Serial Sectioning Microscopy (OSSM), Confocal Laser Scanning Microscopy (CLSM), Surface Plasmon Resonance Microscopy (SPRM), and Reflection Interference Contrast Microscopy (RICM). The basic principles, specifics of implementation, and example applications of each method are presented in order to promote the reader?s understanding of the techniques, so that these may be applied to their own research interests.